Associations between extreme precipitation, drinking water, and protozoan acute gastrointestinal illnesses in four North American Great Lakes cities (2009–2014). (26th April 2022) - Graydon, Ryan C.; Mezzacapo, Michael; Boehme, Jennifer; Foldy, Seth; Edge, Thomas A.; Brubacher, Jordan; Chan, Hing Man; Dellinger, Matthew; Faustman, Elaine M.; Rose, Joan B.; Takaro, Tim K.
Abstract: Climate change is already impacting the North American Great Lakes ecosystem and understanding the relationship between climate events and public health, such as waterborne acute gastrointestinal illnesses (AGIs), can help inform needed adaptive capacity for drinking water systems (DWSs). In this study, we assessed a harmonized binational dataset for the effects of extreme precipitation events (≥90th percentile) and preceding dry periods, source water turbidity, total coliforms, and protozoan AGIs – cryptosporidiosis and giardiasis – in the populations served by four DWSs that source surface water from Lake Ontario (Hamilton and Toronto, Ontario, Canada) and Lake Michigan (Green Bay and Milwaukee, Wisconsin, USA) from January 2009 through August 2014. We used distributed lag non-linear Poisson regression models adjusted for seasonality and found extreme precipitation weeks preceded by dry periods increased the relative risk of protozoan AGI after 1 and 3–5 weeks in three of the four cities, although only statistically significant in two. Our results suggest that the risk of protozoan AGI increases with extreme precipitation preceded by a dry period. As extreme precipitation patterns become more frequent with climate change, the ability to detect changes in water quality and effectively treat source water of varying quality is increasingly important for adaptive capacity and protection of public health. HIGHLIGHTS: We examined binational source water quality of the North American Great Lakes, as measured at the intakes of four drinking water systems (DWSs), along with the precipitation on the risk of cryptosporidiosis and giardiasis in the populations served by the DWSs. When preceded by a dry period, an extreme precipitation week increased the relative risk of acute gastrointestinal illness after 1 and 3–5 weeks for three of the four PWSs studied.